Study on the preparation of selenium nanoparticles by gamma Co-60 method and investigate the stability - Nguyen Ngoc, Duy; Dang Van, Phu; Le Anh, Quoc; Nguyen T. Kim, Lan; Nguyen Quoc, Hien; Tran T. Thu, Ngan (Nuclear Science and Technology, 2020)
Among nanoparticle materials, selenium nanoparticles (SeNPs) have attracted wide spread attention due to their excellent bioavailability, high bioactivity and low toxicity compared to other ionic selenium compounds. SeNPs with size 41.75 nm were synthesized by γ-irradiation method using oligochitosan (OC) as stabilizer. The prepared SeNPs/OC were characterized by UV-Vis spectroscopy and transmission electron microscope (TEM) images. The SeNPs/OC powder was also prepared by spray drying technique and the purity was verified by energy dispersive X-ray (EDX) analysis. The results of EDX showed that SeNPs/OC solution was of high purity. The stability of SeNPs/OC solution was investigated. The results indicated that SeNPs/OC solution had good stability after 60 days of storage at 4ºC. At ambient temperature, the SeNPs/OC solution was unstable and agglomerated after about 15 days. The SeNPs/OC synthesized by γ-irradiation with the advantages of environmental friendly and mass production process may be potentially promising for applications in medicines, functional food and in other fields as well.